Images of Futures : Education Systems and Multiculturalism for Third World Development : Case: eSwatini, UWC and National Education curricula - Reissmann, Mandla (My University, 2021)
This study is exploratory in nature, combining Futures Studies with Ethnographic interview and analysis, while using methods as an Action Research exercise with interviewees. The research question: What are some future images of third world development driven by multicultural education? Firstly, focused on national development of developing countries, from the pragmatic view that education is the main driver for development. I look closely at the United World College (UWC) Waterford Kamhlaba and the eSwatini education systems. Drawing a link between education and multi-culturalism constitutes the answer to a development themed sub-question: Does the national school system of eSwatini benefit from the influence of globalization on both education and business? The overarching issue being addressed in this study is that there are the yet unexplored avenues of development and innovation in education that include issues of equality, competitiveness, quality and delivery of education in a more globally connected learning and working environment. A total of eight interviews were carried out with interviewees in two general groups, Educators and Alumni. They are linked to Waterford Kamhlaba UWC, eSwatini or the discipline of education as experts. Each interview was about half an hour exploring the Futures Studies method of Causal Layered Analysis (CLA) as a form of Action Learning while discussing the ideas of the research questions. Analysis of interview material is a rigorous computer-aided textual analysis that extracts and distils ideas using the CLA method as a framework for image creation. Four imaginative yet logical im- ages of the future in eSwatini’s education systems and the Waterford Kamhlaba UWC are included in the results. These images are combined to assert the existence of a Desired Future which borrows elements of all the four images. The background research and images produced show that there are some key areas to consider changing education in eSwatini from an increase in infrastructure and investment to changes in the outlook of what it means to be a contemporary economy, including ecology and other cycles. Research findings also include suggestions of new directions within UWC as well as eSwatini education systems.
Keywords: Causal Layered Analysis, Ethnographic Interview, Development Economics, UWC, eSwatini, Waterford Kamhlaba, Education, Innovation, Socio-Economic Cycles